ER Stress Depresses NF-κB Activation in Mesangial Cells through Preferential Induction of C/EBPβ - Hayakawa, Kunihiro (American Society of Nephrology, 2010)
Modest induction of endoplasmic reticulum (ER) stress confers resistance to inflammation in glomeruli. Recently, we found that ER stress leads to mesangial insensitivity to cytokine-induced activation of NF-κB, but the underlying mechanisms are incompletely understood. ER stress can trigger expression of CCAAT/enhancer-binding proteins (C/EBPs), which interact with transcription factors including NF-κB. Here, we investigated a role for C/EBPs in the ER stress–induced resistance to cytokines. Mesangial cells preferentially induced C/EBPβ after exposure to thapsigargin or tunicamycin; induction of C/EBPδ was modest and transient, and expression of C/EBPα was absent. The induction of C/EBPβ correlated with accumulation of C/EBPβ protein and enhanced transcriptional activity of C/EBP. Overexpression of C/EBPβ markedly suppressed TNF-α–induced activation of NF-κB, independent of its transacting potential. Knockdown of C/EBPβ by small interfering RNA reversed the suppressive effect of ER stress on NF-κB. In vivo, preconditioning of mice with ER stress induced renal C/EBPβ and suppressed NF-κB–dependent gene expression in response to LPS. Using dominant negative mutants and null mutants for individual branches of the unfolded protein response, we identified the RNA-dependent protein kinase–like ER kinase (PERK) and the inositol-requiring ER-to-nucleus signal kinase 1 (IRE1) pathways as the unfolded protein response responsible for ER stress–induced C/EBPβ. These results suggest that ER stress blunts cytokine-triggered activation of NF-κB, in part through PERK- and IRE1-mediated preferential induction of C/EBPβ.